Genome-Wide Association Studies and Genomic Selection in Pearl Millet: Advances and Prospects - Srivastava, Rakesh K.; Singh, Ram B.; Pujarula, Vijaya Lakshmi; Bollam, Srikanth; Pusuluri, Madhu; Chellapilla, Tara Satyavathi; Yadav, Rattan S.; Gupta, Rajeev (Frontiers in Genetics, 2020)
Pearl millet is a climate-resilient, drought-tolerant crop capable of growing in marginal environments of the arid and semi-arid regions globally. Pearl millet is a staple food for more than 90 million people living in poverty and can address the triple burden of malnutrition substantially. It remained a neglected crop until the turn of the 21st century and since then a lot of emphases were given to develop various genetic and genomic resources for whole-genome scan studies such as the genome-wide association studies (GWAS) and genomic selection (GS). This was facilitated by the advent of sequencing-based genotyping such as genotyping-by-sequencing (GBS), RAD-sequencing and whole-genome re-sequencing (WGRS), etc. in pearl millet. To carry out GWAS and GS, a world association mapping panel called the pearl millet inbred germplasm association panel (PMiGAP) was developed at ICRISAT in partnership with Aberystwyth University. This panel consisted of germplasm lines, landraces and breeding lines from 27 countries, and was re-sequenced using WGRS approach. It has a repository of circa 29 million genome-wide SNPs. PMiGAP has been used to map traits related to drought tolerance, grain Fe and Zn content, nitrogen use efficiency, components of endosperm starch, grain yield, etc. Genomic selection in pearl millet was jump-started recently by WGRS, RAD-and tGBS (tunable genotyping-by-sequencing) approaches for the PMiGAP and hybrid parental lines. Using multi-environment phenotyping of various training populations, initial attempts have been made to develop genomic selection models. This mini-review discusses advances and prospects in GWAS and GS for pearl millet.